2004
DOI: 10.1590/s1413-86702004000500008
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effect of borage (Echium amoenum) on Staphylococcus aureus

Abstract: Borage (Echium amoenum) is a large annual plant of the Boraginaceae family, which grows in most of Europe and in northern Iran. The borage flower is used as a medicinal herb in France and other countries. Iranian borage is used in traditional medicine for infectious diseases, flu and as an anti-febrile. We tested the aqueous extract of borage dried flowers in vitro for its antibacterial activity. The extract showed concentration-dependent antibacterial activity against Staphylococcus aureus 8327. This activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…Many studies have revealed the presence of various phytochemicals in borage plants (tannins, resins, ascorbic acid, beta-carotene, niacin, riboflavin, thiamine, silicic acid, choline arabinose, unsaturated pyrrolizidine alkaloids and polyphenolics [4][5][6][7]). The plants of Boraginaceae family have also shown antibacterial activity against some human pathogens [8][9][10]. Borage is eaten raw in salads or cooked as part of several typical regional preparations.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have revealed the presence of various phytochemicals in borage plants (tannins, resins, ascorbic acid, beta-carotene, niacin, riboflavin, thiamine, silicic acid, choline arabinose, unsaturated pyrrolizidine alkaloids and polyphenolics [4][5][6][7]). The plants of Boraginaceae family have also shown antibacterial activity against some human pathogens [8][9][10]. Borage is eaten raw in salads or cooked as part of several typical regional preparations.…”
Section: Introductionmentioning
confidence: 99%
“…One of these plants is E. amoenum that has been shown as a rich source of antioxidants, such as rosmarinic acid (RA) and flavonoids. Abolhassani (2004) tested the aqueous extract of E. amoenum dried flowers in vitro for its antibacterial activity. The extract showed concentration-dependent antibacterial activity against Staphylococcus aureus 8327.…”
Section: Discussionmentioning
confidence: 99%
“…Echium amoenum (Boraginaceae) is an important medicinal plant in Iranian folk medicine [29]. It has been used as an antidepressant, analgesic, antioxidant, antibacterial treatment as well as cough and sore throat [30,31].…”
Section: Echium Amoneummentioning
confidence: 99%